IASWS - abordagem iterativa para desenvolvimento de software utilizando web services - Nakagawa, Hiromiti (2012)
Software system development demands appropriate tools, technologies and development processes in order to create systems that meet customer s business needs while being flexible enough to cope with business evolution and constant changes. Service-Oriented Computing (SOC) is an IT paradigm that might help on such development as long as a development process is established to address its peculiarities. As part of this work some of these processes were analyzed and it was observed that several of them focus on development of systems composed exclusively by services, which is not always interesting: first when building software s graphical user interface, second when the business logic that gives competitive advantage needs to be encapsulated, or third at enterprises starting the SOC adoption. In these cases a mix of Object-Oriented (OO) elements and SOC principles, concepts, technologies and techniques could be used to provide better results. This work presents an iterative approach to develop software that uses OO and services, named IASWS (Iterative Approach for Software Development using Web Services) based on the Incremental model. It incorporates business process modeling using BPMN; XP and SoaML profile. This approach differs from the others as it allows services and SOC gradual adoption and is comprised of nine phases: Requirements Identification, Business Process (BP) and Services Contextualization, Service Design, Service Implementation, Service Testing, Solution Design, Solution Implementation, Solution Testing and Acceptance Verification. This dissertation is focused on the four initial phases: Requirements Identification, BP and Services Contextualization, Service Design and Solution Design which are responsible for: system requirements gathering, requirements analysis and solution elaboration, service design and solution design. Software increments are delivered as iterations complete and includes the implementation of one or more business process. Delivering software increments to the customer allows for development progress visualization and provides feedback on what had been implemented. Business process modeling using BPMN contributes to understanding customer s business area and improves requirements identification. Services are modeled and specified using SoaML profile allowing automatic code generation at the implementation phase. Two examples applying approach to development were carried out to investigate the IASWS applicability.